The Effects of Different Storage Temperatures and Durations on Peroxide Values of Fish Feed Ingredients - Aysun Kop; Kutsal Gamsız; Ali Yıldırım Korkut; Hülya Sayğı (Turkish Journal of Agriculture: Food Science and Technology)
The growth of fish in intensive fish farming is carried out completely by the feeds supplied from externally. Different ingredients are used in feed production. The nutritional content of these ingredients is checked when purchased or brought to the factory. These ingredients are then stored until feed production. Storage duration and storage temperatures directly affect the freshness criteria of feed ingredient materials. Especially when high-energy ingredients with high levels of fat are stored in poor storage conditions, the fats in the ingredients are oxidized, therefore the peroxide number increases and the ingredient becomes bitter. Oxidation not only destroys the lipids in fish feeds but also vitamins. Slow growth, poor feed evaluation, color darkening, lethargy and deaths have been reported in fish fed with diets that are oxidized and inadequate in vitamin E. In this study, oxidation levels of fish feed ingredients were determined due to different storage conditions. Generally, the number of peroxides increased due to the increase in storage time and temperature, depending on the type of raw materials and oil content.